Causes of mortality in cases with extra nodal natural killer/T-cell lymphoma, nasal type: A cohort study - Mei, Mei (PLoS One, 2019)
OBJECTIVE: Extra nodal natural killer/T-cell lymphoma (ENKTL), nasal type is a rare and highly aggressive type of non-Hodgkin's lymphoma (NHL) commonly presented in the nasal cavity or lymphatic system. However, the common causes of mortality in ENKTL remain unclear. We conducted a retrospective population-based cohort study to elucidate the different causes of mortality in ENKTL and illustrate the main causal and associated risk factors leading to death. METHODS: The study included patients diagnosed with ENKTL from 1987 to 2014 in the Surveillance, Epidemiology, and End Results (SEER) program. Univariate survival analysis was conducted using Kaplan-Meier analysis, and multivariate analyses were performed using Cox proportional hazards regression model. Competing-risks regression model was applied to estimate specific risks associated with mortality. RESULTS: The analysis demonstrated increased mortality in males and patients diagnosed at older age and higher disease stage. NHL was the most common cause of mortality in patients with ENKTL, accounting for 74.13% of deaths in the cohort, followed by other malignant cancers, heart diseases, and infection. However, NHL-specific death events were fewer in patients diagnosed with advanced disease stage compared with incidences of death by other causes such as disease of heart and infections. Significant difference was seen between patients diagnosed earlier than 2000, who showed a higher probability of dying from NHL, and those diagnosed later, who showed propensity to die from other malignant tumors and infection. No differences were found when comparing sex or age at diagnosis. CONCLUSION: The most common cause of mortality in cases with ENKTL-NT is NHL. The female sex, diagnosis at young age and early stage are associated with improved prognosis. Further, the classification of Ann Arbor stage and year of diagnosis can provide references of specific causes of death, which might help decrease the mortality rate.